HUBUNGAN TINGKAT KECERDASAN LINGUISTIK DENGAN HASIL BELAJAR BAHASA INDONESIA DI KELAS VI B01 MI AL ZAYTUN INDRAMAYU - Ichdha Kurnia; Wiena Safitri (JOEL: Journal of Educational and Language Research, 2022)
Language skills are important for learning process. A student cannot learn well if he does not understand the language of instruction. So the level of linguistic intelligence is needed to get good exam result. Based on that case, this study aims to determine whether there is a relationship between the level of linguistic intelligence and Indonesian language exam results. This research is correlational research. The population of tis research were students of class VI B 01 MI Al Zaytun. The sampling technique in this research was saturated sample, The sample was the entire population of 28 students. In this research, linguistic intelligence level is an independent variable, and the exam results of Indonesian language as dependent variable. The prerequisite analysis test was carried out by testing the normality of the data. The data normality test use a histogram for each variable and the Kolmogorov-Smirnov formula. The hypothesis in this research proof by using the Product Moment Pearson. The results showed that: (1) There is a relationship between the level of linguistic intelligence and Indonesian language exam results in class VI B 01 students at MI Al Zaytun Indramayu; (2) The relationship in the percentage analysis is in medium criteria; (3) The relationship in Pearson Product Moment analysis is at a low criteria; (4) The relationship is generally stated to be in the medium category which tends to be low. We should give an attention to the growth of interest in reading, writing and speaking so that the level of linguistic intelligence can be categorized as high.